Work inclusive methodology in a social exclusion zone. Educational compensation and Interculturality. - Amaro Agudo, Ana (Historia y Comunicación Social, 2014)
The law, to guarantee the fundamental right to education of all students, the educational attention for students with Specific Needs of Educational Support associated to disadvantaged social conditions with a set of steps and actions of acompensating nature. Today’s society demands a change in classrooms and example of it has been collected in this article with the inclusive methodology carried out in Luisa de Marillac Centerin the city of Granada (Spain).
Keywords: Educational compensation; Interculturality; Inclusion; Rome Project.